European migration : what do we know? - Zimmermann, Klaus F. (Oxford University Press, 2005)
Developed countries, especially in Europe, face a number of issue related to migration: social and economic disruptions caused by the declining demand for unskilled labour and resulting unemployment, a shortage of skilled labour in many professions, increasing international competition for highly qualified human capital, radical demographic changes, and the forthcoming expansion of the European Union, which will trigger further immigration into major European countries and createnew market opportunities in Central and Eastern Europe. This suggests a need for a deeper knowledge of the causes and.